Impaired perfusion in the myocardial microcirculation in asymptomatic patients with Stages 1–4 chronic kidney disease with intrarenal arterial lesions. Issue 11 (1st December 2020) - Xiao, Fei; Zhang, Weiwei; He, Ya-Ni; Yang, Jie; Liu, Xinghong; Wang, Ling; Zhang, Jianguo; Dai, Huanzi
Abstract: Background: Even mild renal disease is a powerful cardiovascular risk factor. However, the association between these pathophysiologic processes (especially in the early asymptomatic stage) is not known. Methods: We recruited 243 asymptomatic patients with Stages 1–4 chronic kidney disease (CKD) without obstructive coronary artery disease (CAD). We distinguished different degrees of severity of intrarenal arterial lesions (IALs) according to the Oxford classification. Myocardial microcirculation perfusion was measured using single-photon emission computed tomography (SPECT). Summed scores of 17 stress and rest image segments produced the summed stress score (SSS) and summed rest score (SRS), respectively. The summed difference score (SDS) was calculated as the difference between the SSS and SRS. Coronary microvascular disease (CMD) was defined as abnormal SPECT (SSS ≥4 or SDS ≥2) in the absence of obstructive CAD. Results: Participants showed a stepwise increase in CMD severity with IAL aggravation. SSS of no/mild/moderate/severe IALs was 1.64 ± 1.08, 2.56 ± 1.35, 4.42 ± 2.17 and 6.48 ± 3.52, respectively (P < 0.05 for all). SDS of no/mild/moderate/severe IALs was 1.29 ± 0.49, 1.75 ± 0.56, 3.06 ± 1.12 and 4.16 ± 1.85, respectively (P < 0.05 for all). The percentage of subclinical CMD in CKD patients with IALs was significantly higher than in those without IALs (69.57% versus 14.71%; P = 0.01). Multiple regression analysis showed that renal arteriolar hyalinization (odds ratio = 1.578, P = 0.009) was associated independently with subclinical CMD. Conclusions: We demonstrated, for the first time, that impaired perfusion in the myocardial microcirculation in asymptomatic patients with Stages 1–4 CKD with IALs. Renal arteriolar hyalinization may be a useful marker of CMD in CKD.